Universities’ Role in Addressing Terrorism in Light of Students’ Awareness to its Definition, Causes, and Types - Al Zou’bi, Reem (European Scientific Journal, ESJ, 2017)
The study aims to explore the degree of awareness of Jordanian education college students to terrorism’s definition, type and causes, and the universities’ roles in addressing terrorism. A five- scale questionnaire was designed by the author and administrated to 130 students studying at the faculty of education, Al-al Bayt University. The external reliability coefficient for the total questionnaire domains was 0.84, and the internal reliability coefficient (Cronbach Alpha) for the total questionnaire domains was 0.88. This indicates that the questionnaire was reliable and suitable for a sample administration. The results indicated that students were aware of the concept and types of terrorism, but they have a misconception of its main causes. These, however, were relevant from the perspectives of economical and social causes. Students’ misconception can be interpreted by students’ social alienation, and their refusal based on economic and social circumstances. The author suggested that universities must hold intense rehabilitating programs for the youths. This is in addition to holding international conferences on human security as it could raise students’ awareness of terrorism and help them in addressing it eventually.